A psychometric analysis of the Caring Assessment Tool version V. Issue 3 (21st April 2019) - Sim, Jenny; Lapkin, Samuel; Joyce, Joanne; Gordon, Rob; Kobel, Conrad; Fernandez, Ritin
Abstract: Aim: The aim of this study was to examine the factor structure and construct validity of the Caring Assessment Tool version V (CAT‐V) for patients in Australian hospitals. Design: Secondary analysis of CAT‐V surveys from the Australian Nursing Outcomes Collaborative (AUSNOC) data set was used. The CAT was originally developed in the United States of America. Methods: The 27‐item CAT‐V was administered to patients prior to discharge from eight wards in three Australian hospitals in 2016. The psychometric properties of the CAT were evaluated using item analysis and exploratory factor analyses. Results: Item analysis of surveys from 476 participants showed high levels of perceived caring behaviours and actions. Exploratory factor analysis revealed a two‐factor structure consisting of: Nurse–patient communication; and Feeling cared for . The CAT‐V is a reliable and valid instrument for measuring patients' perceptions of the attitudes and actions of nurses in Australia.